Does Educational Choice Erode the Immigration Surplus? - Wido Geis (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
Many countries pursue an immigration policy that is targeted at attracting high skilled workers. Borjas (1995) has shown that assuming perfect labor markets immigration leads to a welfare gain for the native population, the so-called immigration surplus. Thus, as the labor market for high skilled workers exhibits few frictions, high skilled immigration should lead to a welfare gain. Nevertheless, this argumentation implicitly assumes that immigration has no influence on the qualification structure of natives. In this paper I show that if natives anticipate high skilled immigration, fewer natives acquire a high education level. In labor markets that are not frictionless this effect can be such strong that high skilled immigration leads to a welfare loss for natives. Moreover, if high skilled migration is expected but not realized, this expectation generates a welfare loss.
Keywords: H62; J24; J61; 330; Immigration; native welfare; education structure; immigration surplus; Einwanderung; Hochqualifizierte Arbeitskräfte; Bevölkerung; Bildungsverhalten; Qualifikation; Wohlfahrtsanalyse; Theorie